The Effect of Financial Reporting on Company Value The Impact of Company Financial Statement Fraud - Marjohan, Masno; Adhe Purnomo, Nugroho; Dwi Pratama, Guruh (Universitas Muhammadiyah Surakarta, 2023)
The purpose of the study is to find out and analyze more deeply the impact of financial statement fraud on the value of companies in the housing construction sector. We use panel data analysis to uncover connections between external pressures, industry research, and financial statement fraud. We know financial fraud is common in developed countries among property developers, but relatively limited in developing countries. Investors play an important role in diamond fraud and financial statement fraud, as they significantly affect the value of the company. So, accurate information that reflects actual conditions without resorting to fraudulent practices. Transparency in financial reporting is essential to safeguard the interests of internal and external stakeholders. We suggest enhancing the role of Internal Audit and implementing robust risk management measures to strengthen internal control mechanisms and enable business expansion and innovation. Our main goal is to eradicate financial fraud, thereby increasing the overall value of companies in the Property and Real Estate sector.